Additionality of public R&D funding for business R&D – a dynamic panel data analysis. (1st January 2012) - Bloch, Carter; Graversen, Ebbe Krogh
An important issue in R&D policy is whether publicly funded R&D is a substitute or a complement to privately funded R&D. However, measuring the impact of R&D policies has proven a difficult task, complicated by simultaneity and selection bias. We utilise a dynamic panel data approach to examine the effect of public funding that takes account of both these potential biases, using R&D data for Danish firms from 1995 to 2005. We find robust evidence of significant complementary effects, with a 1% increase in public funding yielding around a 0.12% increase in privately funded R&D. For predicted values of public funding for both R&D active firms that have and have not received public funding, estimates are slightly lower, at around 0.09%.